Seismic and infrasound observations at Syowa Station and surrounding region of Antarctica - Sciece targets and data management for long-term monitoring - - Masaki, Kanao; Seiji, Tsuboi; Masa-yuki, Yamamoto; Takahiko, Murayama; Yoshiaki, Ishihara; Manami, Nakamoto; Takeshi, Matsushima; Shigeru, Toda (2017)
第8回極域科学シンポジウム/横断セッション：[ID] 極域データサイエンス 12月8日（金）国立極地研究所 3階セミナー室 The Eighth Symposium on Polar Science/Interdisciplinary sessions: [ID] Polar data science Fri. 8 Dec./3F Seminar room, National Institute of Polar Research conference object